Combination ‘v lyubom sluchaye’ (any way): Functioning in Text and Pragmatic Potential - N. Yu. Pilyugina (Научный диалог, 2022)
The article is devoted to the description of text structures based on a combination ‘v lyubom sluchaye’ (any way). The analysis was carried out on the material of the texts of the newspaper subcorpus of the National Corpus of the Russian Language. The relevance of the study is due to a multidimensional approach to describing the textual nature of connectivity, including the use of a cognitive-semantic approach to the study of a text from the standpoint of the speaker’s intention, which is consistent with the anthropocentric paradigm of modern linguistics. Within this paradigm, special attention should be paid to transitional linguistic units that occupy an intermediate position between official and significant lexemes and are used by the speaker to form a certain semantic task into a text structure, defined in the article through the concept of a text structure. As an example of such a unit, the combination ‘v lyubom sluchaye’ (any way) is used. It is shown that at a certain position in the text on the border of the utterance, the combination performs the function of a text clip, forms standard text blocks. Particular attention is paid to the analysis of scenarios and models for the presentation of information on the material of newspaper discourse texts. The results of the modality analysis of the of right side the of the structure, which determines the explication of one of the two meanings of the clip ‘free choice’ and ‘universality’ is presented in the article. It is described how the pragmatic potential of the combination is realized in the structure of the textual construction ‘v lyubom sluchaye’ (any way), depending on the nature of the alternative circumstances of the left side of the structure (options, conditions, opinions, assumptions).